Clinical Profile of Birth Asphyxia in Rajshahi Medical College Hospital (TAJ: Journal of Teachers Association, 2009)
Birth asphyxia is an important cause of preventable cerebral injury in the neonatal period. It continues to be major cause of neonatal mortality and morbidity in both developing and developed countries. Recently a quite good number of birth asphyxiated new born babies had been admitted in the pediatric department of RMCH (Rajshahi Medical college Hospital). This study has been conducted to see the types and outcome of management of birth asphyxiated babies. A total 871 neonates were admitted in the pediatric department of RMCH from September 2001 to November 2002. Out of which birth asphyxia was 191 (21.92%) acute respiratory infection (ARI)-194 (22.73%), Low birth weight (LBW)-113 (12.97%), Neonatal jaundice-84 (9.64%), Septicaemia-38 (4.38%), Meningitis-26 (2.98%), Diarrhea-24 (2.75%), Birth trauma-24 (2.75%), Neonatal tetanus-04 (0.45%), Out of the total birth asphyxiated babies, mild type was 35 (18.32%), moderate type was 40 (20.94%), and severe birth asphyxia was 116 (60%), The recovery rate in mild birth asphyxia was (100%), in moderate case was (95%) and in severe case the rate was (74.13%).   doi: 10.3329/taj.v18i2.3176 TAJ 2005; 18(2):  106-108